Carotenoids, total polyphenols and antioxidant activity of grapes (Vitis vinifera) cultivated in organic and conventional systems - Bunea, Claudiu-Ioan (BioMed Central, 2012)
BACKGROUND: Organic agriculture involve plants which are cultivated without using synthetic pesticides, herbicides or fertilizers and promotes biodiversity, biological cycles and improve the product quality. The carotenoids, total polyphenols and the antioxidant activity from skins of some wine and table grapes cultivated in organic and conventional agriculture were studied. RESULTS: The main carotenoids identified using high performance liquid chromatography were lutein and ß-carotene. Muscat Ottonel variety has the highest ß-carotene concentration 504.9 μg/kg for organic and 593.2 μg/kg for conventional grapes. For the organic farming, the total polyphenols content were in the range of 163.23 – 1341.37 mg GAE/kg fresh weight (FW) and 148.47 – 1231.38 mg GAE/kg FW for the conventional grapes. The highest ORAC values were obtained for blue-black variety Napoca in both farming system (43.5 ± 0.95 μmol TE/g organic; 40.4 ± 0.5 μmol TE/g conventional) and lowest for Aromat de Iaşi (16.8 ± 0.6 μmol TE/g organic; 14.7 ± 1.6 μmol TE/g conventional). Napoca variety showed also the highest antioxidant activity measured by DPPH method in both cultivated system. CONCLUSION: Nine grape varieties cultivated in organic and conventional systems were compared regarding the carotenoids, total polyphenols and antioxidant activity. The white grape varieties have a higher carotenoids content compared with the blue-black cultivars while the blue-black varieties contain higher TPC and exhibit higher antioxidant activity (except for Muscat Hamburg-ORAC). Vitis vinifera grape skins originating from wine or table grape varieties can be used as a potential source of natural antioxidants.